Freedom and democracy for Greece. Down with the military dictatorship! (World Federation of Democratic Youth, 1974)
Black and white photograph of demonstration, cropped in shape of the map of Greece; silhouettes of bayonets pointing at it Poster advertising international youth seminar, held in Dusseldorf, 27-28 April, 1974 PO-1578